Penyuluhan Pencegahan Kekerasan Perempuan dan Anak Pada Yayasan Pendidikan Al-Yasiriyah Bersaudara - Lili Nurmaliza; Nur Azizah Lubis; Juliana Sion Sihombing; Muhammad Bagas F; Andilala; Muhammad Arif Fadhillah Lubis; Salim (Jurnal Pengabdian Masyarakat, 2023)
Acts of violence usually occur against helpless victims, especially women and children. In fact, this act of violence occurred in the environment closest to the victim, for example, the neighborhood or school, and was carried out by perpetrators who were supposed to protect women and children. This is usually caused by a low level of knowledge about the dangers of violence, especially on the victim's side. So it is necessary to carry out an educational program to prevent acts of violence against women and children in an effort to support government programs to minimize these actions. Counseling activities were carried out at the Al-Yasiriyah Brothers Education Foundation. Counseling is carried out with the mechanisms of the lecture method, discussions, and mini games, which aim to provide an interactive counseling impact that can meet the target of understanding the participants' understanding regarding information on preventing violence against women and children. The results of the counseling show that satisfaction with the implementation of the extension activities had an impact on increasing the knowledge of the extension participants, with a percentage score of 86%. With a description, each participant gave an assessment of being in the good category in the implementation of the extension activities. While the average assessment given by extension participants on the implementation of activities has an assessment level of 3.45, This counseling activity is expected to broaden the participants' insights regarding the impact and strategies for preventing violence in everyday life, especially for women and children.